Selenium uptake, differentiation and metabolism in hyperaccumulator Stanleya pinnata - Harris, Jonathan, author; Pilon-Smits, Elizabeth, advisor; Pilon, Marinus, committee member; Peers, Graham, committee member; Ward, Sarah, committee member (Colorado State University. Libraries, 2013)
Selenium (Se) is a biologically essential element for many animals, some prokaryotes and algae. However, even in organisms that require Se, the range between sufficiency and toxicity for Se is narrow. Although there are no reports of a Se requirement or selenoproteins in higher plants, there are species that appear endemic to seleniferous soil and concentrate Se in their leaves to levels exceeding 1000 mg kg-1 dry weight. These plants are known as Se hyperaccumulators and have an exceptional ability to tolerate and enrich themselves with this toxic element. As a result of the Se concentrations in their tissues, Se hyperaccumulators are extremely toxic to most organisms. Studies have found that Se hyperaccumulation protects these plants from many herbivores and pathogens as an "elemental defense." Some of these hyperaccumulators have been studied for their use in phytoremediation of naturally occurring and anthropogenically contaminated seleniferous soils. Although the slow growth of most hyperaccumulators limits their direct application for phytoremediation, they can be utilized as a source of genes to genetically enhance Se accumulation and tolerance in popular phytoremediator species. The goal of this study is to better characterize the uptake, metabolic fate and molecular mechanisms responsible for Se tolerance in Stanleya pinnata, a hyperaccumulator in the Brassicacae. Two main techniques were utilized: physiological experiments followed by elemental analysis to characterize Se uptake and interactions with the related element sulfur (S), and Illumina sequencing of the transcriptomes of Stanleya pinnata and related non-hyperaccumulator Stanleya elata. The first chapter presents a literature review of Se hyperaccumulation: what is known about Se assimilation in higher plants, and some unique characteristics of hyperaccumulators. The metabolism of Se through the sulfate assimilation pathway is described, and known mechanisms of Se tolerance and accumulation in representative plants are reviewed. In addition, some of the previous work on Stanleya is reviewed, including a number of studies that have shown ecological benefits of Se hyperaccumulation. Known beneficial genes for Se tolerance and accumulation are discussed in the context of phytoremediation. In chapter 2, Se-specific uptake was tested in two ecotypes of S. pinnata, and contrasted with related non-hyperaccumulator Brassica juncea. To test for Se specificity of sulfate transporters, plants were supplied with varying concentrations of selenate and two concentrations of sulfate. The results showed that S. pinnata is able to take up large amounts of Se, even at exceedingly low supplied Se:S ratios. In addition, S. pinnata preferentially mobilized large amounts of Se to young leaves, without commensurate mobilization of S. These trends were not observed in the non-hyperaccumulator B. juncea, which showed dramatically reduced Se uptake under elevated sulfate supply. Moreover, there was no evidence of preferential allocation of Se to young tissues in B. juncea. Taken together, these findings support the hypothesis that Stanleya contains transporters with an increased specificity for Se, allowing it to take up preferentially and mobilize Se over S. Since previous work has shown that molybdate may be taken up in part by plant sulfate transporters, this element was also monitored. It was observed that increasing supply of selenate and sulfate significantly reduced the molybdenum (Mo) content of leaves in S. pinnata. In contrast, B. juncea showed an increase in Mo content with increases in supplied selenate. In the experiment described in Chapter 3, Illumina sequencing was performed to compare the root and shoot transcriptomes of hyperaccumulator S. pinnata and non-hyperaccumulator S. elata in the presence or absence of selenate. An overview is presented of the overall transcriptome response patterns, followed by a more detailed analysis of transcripts involved in S/Se metabolism. In the presence of Se, 40 of the 56 S/Se-related genes were more highly expressed in S. pinnata than S. elata. Particularly promising findings include a vastly upregulated root sulfate/selenate transporter (Sultr1;2) and ATP sulfurylase (APS2). Lastly, some preliminary findings are presented from several biochemical approaches used to further investigate S. pinnata hyperaccumulation mechanisms. Organic forms of Se were investigated in S. pinnata and S. elata using a newly developed liquid chromatography mass spectrometry (LC-MS) method. It was shown that S. pinnata accumulates significant amounts of selenocystathionine as well as methyl-selenocysteine. Moreover, activities of selenocysteine lyase (SL) and cysteine desulfurase (CysD) were investigated in S. pinnata and S. elata, which revealed strong SL activity in the hyperaccumulator. The possible role of this enzyme in Se hyperaccumulation remains to be elucidated. Finally, superoxide dismutase activities were compared between the two species in relation to Se supply. Stanleya pinnata and other Se hyperaccumulators may be valuable resources for genes involved in Se tolerance and hyperaccumulation, to create genetically engineered plants for phytoremediation purposes. In addition to the potential environmental benefits, understanding potential biological roles for Se and its metabolism in these plants may have broad applications for human health. Many organic seleno-compounds have been studied for their anti-carcinogenic properties in multiple systems and types of cancer. Efficacy of these Se compounds appears to vary based on the form of Se. Plants capable of creating different forms of organic Se may become a valuable pharmaceutical resource.
Keywords: hyperaccumulators; selenium; Stanleya pinnata